Bio‐economic efficiency of creep supplementation of forage legumes or concentrate in pasture‐based lamb production system. (7th April 2017) - Ates, S.; Keles, G.; Yigezu, Y. A.; Demirci, U.; Dogan, S.; Isik, S.; Sahin, M.
Abstract: A 2‐year study in the Central Anatolian Region of Turkey compared the performance of pasture‐fed suckling lambs and their dams, set‐stocked on grass‐legume pastures supplemented either with forage legumes or concentrate through a creep grazing/feeding system in a randomized block design. The treatments included continuous pasture grazing + creep grazing alfalfa; continuous pasture grazing + creep grazing birdsfoot trefoil; continuous pasture grazing + creep feeding concentrate (170 g kg −1 CP; 11.3 ME MJ kg −1  DM); and continuous grazing without creep feeding (control). In both years, creep feeding/grazing commenced in early June following a 42‐day pasture grazing period (period 1) and continued until mid‐summer for two separate periods of 21 days each (periods 2 and 3). Creep‐supplemented lambs grew faster ( p  < .001) than those that grazed pasture alone, with no significant difference across all creep supplementation treatments. Across the years, the lambs grew at 223 and 161 g per head day −1 for creep‐supplemented and control groups respectively. None of the lamb feeding strategies affected the ewe liveweight gains ( p  > .05). Results from a bio‐economic optimization model, however, showed that supplementing the pasture with birdsfoot trefoil and alfalfa in periods 2 and 3, respectively, maximized economic returns with an extra profit of US$88.83 per lamb above those that grazed the pasture alone.